2019
DOI: 10.20525/ijrbs.v8i4.288
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vendor Characteristics and Relationship Quality on Consumer Re-Purchase Intention in the B2C E-Commerce in Yemen

Abstract: This study attempted to establish the relationship between vendor characteristics and relationship quality on consumer B2B E-commerce in Yemen. E-commerce is gaining a lot of attention especially in the Arabian world, as such we formulated and tested a model to explain B2C user repurchase intention from the perspective of relationship quality. The model was empirically tested through a survey conducted in Yemen. Results showed that online relationship quality and perceived website usability positively impacted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…The analysis revealed results that were both consistent with earlier research and in conflict with other research. For example, the findings regarding the perceived reputation of an online vendor are consistent with previous studies (Bashir et al, 2018;Gefen & Straub, 2004;Hadi et al, 2019;Hidayanto et al, 2014;Kim et al, 2009;Widiyanto & Prasilowati, 2015). However, some studies have contradicted this perspective (Agus et al, 2020).…”
Section: Research Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The analysis revealed results that were both consistent with earlier research and in conflict with other research. For example, the findings regarding the perceived reputation of an online vendor are consistent with previous studies (Bashir et al, 2018;Gefen & Straub, 2004;Hadi et al, 2019;Hidayanto et al, 2014;Kim et al, 2009;Widiyanto & Prasilowati, 2015). However, some studies have contradicted this perspective (Agus et al, 2020).…”
Section: Research Discussionsupporting
confidence: 88%
“…Nguyen et al (2022) emphasize the significance of brand reputation in attracting consumers to specific e-commerce platforms. The investigation revealed the pivotal role of the company's reputation in the realm of marketing, exerting influence on consumer expectations and purchase decisions (Abdulrab Hadi et al, 2019;Yixiang Zhang et al, 2011). Merchant reputation is found to be shaped by factors like customer feedback, innovation, product quality, and dedication to customer satisfaction (Kong and Hung, 2006;Zhang et al, 2011).…”
Section: Factors Impact Consumer Trust Towards E-commercementioning
confidence: 99%
“…Numerous studies have indicated that the characteristics of E-commerce encompass the characteristics of both the Buyer-side and the Seller-side of E-commerce. The characteristics of E-commerce Buyer-side typically manifest as user-generated content characteristics, while the characteristics of E-commerce Seller-side characteristics often appear as platform characteristics and seller-generated content characteristics (Hadi et al, 2019;Mu & Zhang, 2021;Soleimani, 2022;Tandon et al, 2021;Tsurel et al, 2020;Mingkun, 2021;Yan, 2023).…”
Section: The Characteristics Of E-commercementioning
confidence: 99%
“…The potential for growth in Yemen's e-commerce sector is on an upward trajectory, making it an enticing prospect for budding enterprises. [8,12,[21][22][23][24][25][26][27] Underserved market E-commerce in Yemen is in its nascent stages, and a large portion of its potential clientele remains untapped. This scenario creates an opening for new entrants to claim market share and solidify their position as industry front-runners.…”
Section: Opportunities Description and Rationale Referencesmentioning
confidence: 99%
“…This shift in consumer demographics paves the way for more targeted marketing strategies and product diversification, enabling e-commerce businesses to cater to evolving consumer preferences and cultural norms. [9,12,21,[23][24][25][26][31][32][33][34] Increased internet penetration Yemen's growing internet penetration presents an opportunity for e-commerce startups to reach a larger audience and expand their customer base, as more Yemenis gain access to the internet and mobile devices. The parallel growth in e-commerce and internet accessibility is mutually reinforcing, with increased connectivity leading to more e-commerce activities, and vice versa, contributing to an interconnected and digitally savvy society.…”
Section: Opportunities Description and Rationale Referencesmentioning
confidence: 99%